Why do most young women not take up contraceptives after post-abortion care? An ethnographic study on the effectiveness and quality of contraceptive counselling after PAC in Kilifi County, Kenya - Mercy Kadzo Mwadhi; Martin Bangha; Shelmith Wanjiru; Michelle Mbuthia; Grace Kimemia; Kenneth Juma; Jane Shirima; Shilla Unda; Anne Achieng; Jonna Both; Ramatou Ouedraogo (Sexual and Reproductive Health Matters, 2023)
AbstractPost-abortion care (PAC) counselling and the provision of contraceptive methods are core components of PAC services. Nevertheless, this service is not uniformly provided to PAC patients. This paper explores the factors contributing to young women leaving health facilities without counselling and contraceptive methods. The paper draws from an ethnographic study conducted in Kilifi County, Kenya, in 2021. We conducted participant observation in health facilities and neighbouring communities, and held in-depth interviews with 21 young women aged 15–24 who received PAC. In addition, we interviewed 11 healthcare providers recruited from the public and private health facilities observed. Findings revealed that post-abortion contraceptive counselling and methods were not always offered to patients as part of PAC as prescribed in the PAC guidelines. When PAC contraceptive counselling was offered, certain barriers affected uptake of the methods, including inadequate information, coercion by providers and partners, and fears of side effects. Together, these factors contributed to repeat unintended pregnancies and repeat abortions. The absence of quality contraceptive counselling therefore infringes on the right to health of girls and young women. Findings underscore the need to strengthen the capacities of health providers on PAC contraceptive counselling and address their attitudes towards young female PAC patients.